CO2 Laser Cutting Of Ceramic Tiles - Muhammad Qusyairi , Abdul Rahman (UTeM, 2009)

(untitled)
This project will cover the cutting of commercially-available ceramic tiles by using a CO2 laser cutting machine, with the object of producing a laser beam machining (LBM) database that contains the essential parameter information for their successful processing. Various laser cutting parameters were investigated that would generate a cut in ceramic tile which required minimal post-treatment. There are three main objectives during the accomplishment of this project. The first is to determine the capability of CO2 laser cutting machine in cutting the ceramic tiles. The parameters that have controlled are power input of the CO2 laser cutting, pressure and the cutting speed. Besides that, the second objective is to know whether or not the CO2 laser cutting machine make the engraving process. Then the last objective is to identify the suitable setting of parameters in cutting and engraving the ceramic tiles. The literature review covered the principles of the characteristic of the high power fiber laser, CO2 laser and Nd: YAG laser as well as the principle of laser cutting. To get the measurement of the result, a laboratory test will do to carry out the result of kerf width produced by laser cutting process practically.